2015
DOI: 10.1111/1751-7915.12268
|View full text |Cite
|
Sign up to set email alerts
|

Inoculum selection influences the biochemical methane potential of agro‐industrial substrates

Abstract: Obtaining a reliable estimation of the methane potential of organic waste streams in anaerobic digestion, for which a biochemical methane potential (BMP) test is often used, is of high importance. Standardization of this BMP test is required to ensure inter-laboratory repeatability and accuracy of the BMP results. Therefore, guidelines were set out; yet, these do not provide sufficient information concerning origin of and the microbial community in the test inoculum. Here, the specific contribution of the meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(46 citation statements)
references
References 44 publications
3
39
2
2
Order By: Relevance
“…The average methane production during this period was about 355 L kg −1 VS. It should be noticed that in the work of De Vrieze et al a value of 363 L kg −1 VS was observed in batch reactors anaerobically treating molasses wastewater. The steady‐state conditions, as well as the methane production of about 98% of the aforementioned value, indicate that the sludge was already acclimated on day 62.…”
Section: Resultsmentioning
confidence: 94%
“…The average methane production during this period was about 355 L kg −1 VS. It should be noticed that in the work of De Vrieze et al a value of 363 L kg −1 VS was observed in batch reactors anaerobically treating molasses wastewater. The steady‐state conditions, as well as the methane production of about 98% of the aforementioned value, indicate that the sludge was already acclimated on day 62.…”
Section: Resultsmentioning
confidence: 94%
“…For example, spectra profiles of activated sludge from Min-Sheng WTP (Taipei, Taiwan) [10] and IDARS were different. Sludge from Min-Sheng WTP showed high content of total carbohydrates, and it was the main component among other organic substances.…”
Section: Discussionmentioning
confidence: 99%
“…An active inoculum is crucial for fast and complete degradation of the substrate in a BMP test. Its impact has been demonstrated in previous studies (De Vrieze et al, 2015;Koch et al, 2017). It is not always possible to start an experiment right after collecting the inoculum, although inocula "should be used as fresh as possible" (Holliger et al, 2016).…”
Section: Impact Of Inoculum Storage On Smp Curvesmentioning
confidence: 99%